1980
DOI: 10.1080/00039896.1980.10667486
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of Blood and Hair Mercury Concentrations in a North American Population Exposed to Methylmercury

Abstract: Samples of blood and head hair were analyzed for organic and inorganic mercury from a population which consumed large amounts of fish contaminated with methylmercury. Mercury levels in newly formed hair were found to reflect those in blood with the concentration in hair being approximately 300 times that in blood. Organic and inorganic mercury levels were linearly related in both hair and blood samples, with a mean inorganic/organic ration of 0.05 in blood and 0.21 in hair, but individual differences were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(109 citation statements)
references
References 4 publications
5
95
1
3
Order By: Relevance
“…Em 12 adultos, grandes consumidores de peixes, encontrou a concentração média de 35,06 mg/g. Phelps e col. 16 verificaram entre indígenas canadenses, grandes consumidores de peixe contaminado com metilmercúrio, a concentração média de 13,8 ± 3,6 mg/g de mercúrio total em cabelo.…”
Section: Resultsunclassified
“…Em 12 adultos, grandes consumidores de peixes, encontrou a concentração média de 35,06 mg/g. Phelps e col. 16 verificaram entre indígenas canadenses, grandes consumidores de peixe contaminado com metilmercúrio, a concentração média de 13,8 ± 3,6 mg/g de mercúrio total em cabelo.…”
Section: Resultsunclassified
“…The mercury concentration in hair (microgram Hg/g hair) is proportionally higher than the blood mercury concentration (microgram Hg/L blood) by 250-300 times 28,29) . Mercury is included in a hair strand from the very beginning of the hair's growth, and is retained for the life of the strand.…”
Section: Methylmercury Poisoning In Iraqmentioning
confidence: 99%
“…Scalp hair is also a good indicator for estimating methylmercury exposure 28) . Methylmercury is incorporated into scalp hair at the hair follicle in proportion to its content in blood.…”
Section: Exposure Markers For Methylmercurymentioning
confidence: 99%
“…Measurements of total mercury and methylmercury levels in blood and hair are both used to characterize exposures from fish (Haxton et al, 1979;Sherlock et al, 1982;Airey, 1983;Suzuki, 1988;Oskarsson et al, 1990;ATSDR, 1995). Under steady dietary conditions, blood and hair may be used to predict possible health effects of methylmercury exposure since the concentrations are directly proportional to the levels of methylmercury that occur in the brain (Phelps et al, 1980;Cernichiari et al, 1995a). Studies wih methylmercury labeled with radioactive 203 Hg have shown that methylmercury is nearly all absorbed from the diet, is distributed throughout the body within a few hours, and attains peak blood levels within 4 ±14 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Once formed, the hair strand grows at a rate of approximately 1 cm /month, providing a record of previous mercury exposures that remains unchanged for periods up to at least 11 years (Suzuki, 1991). Approximately 80% of the mercury present in the strand is methylmercury (Phelps et al, 1980;Cernichiari et al, 1995b). Although both hair and blood samples can be used to document methylmercury exposure, hair-strand analysis is preferred because it provides a simple, noninvasive sampling procedure that allows monitoring of methylmercury intake.…”
Section: Introductionmentioning
confidence: 99%